Corrosion protection assessment of nanoparticulate pre-treated galvanized steel/paint systems subjected to accelerated tests - Elsner, Cecilia Ines (2016)
The development of environmentally friendly anticorrosive systems providing the same performance than those already existing has been the great challenge for researchers working in the surface treatment field. In this work the corrosion behavior of two electrogalvanized-steel/nanoparticulate pretreatment/organic coating systems exposed to salt spray, controlled humidity and temperature, Prohesion or weathering chambers was studied. The global analysis of the obtained results allowed concluding that the protective behavior of both duplex systems was satisfactory, and that the nanoparticulate pretreatments based on trivalent chromium (Cr3+) and Zirconium could be considered as a valid alternative to substitute those based on hexavalent chromium(Cr6+).